STUDY OF GLUCOSE SYRUP PRODUCTION FROM MALTODEXTRINES USING TWO COMERCIAL ENZYMES - BETTÍN S., Luz A.; QUINTERO D., Juan C. (Vitae, 2010)
Hydrolyzed starch with a high-dextrose equivalent is extensively used in the food industry and as a source of fermentable sugars. In order to obtain a better yield in this process more efficient enzymes had been continuously developed. Dextrozyme GA® (DGA) has been released recently in the market to replace AMG 300L® (AMG) enzyme. In this paper yields and hydrolysis rates were evaluated as a function of maltodextrin concentration between 60 and 180 g/L and enzymes concentration between 0.188 and 0.75 AGU/mL. DGA allows enhancing hydrolysis rates up to 26 times more than those using AMG. Also DGA generates conversion of maltodextrin up to 95% in less than 60 minutes, in comparison with AMG which produces conversions up to 50% in 8 h. Among the values of substrate and enzyme concentration studied it was found that a substrate concentration of 130.2 g/L and enzyme concentration of 0.55 AGU/mL were optimal values. DGA is inhibited by uncompetitively product and is highly affected at a low enzyme concentration. We developed a mathematical model that successfully reproduces the experimental data. These results could be used in reactors design for syrup glucose enzymatic production.